1998
DOI: 10.1074/jbc.273.48.32304
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Cholesterol Is a Key Molecule in Shear Stress-dependent Activation of Extracellular Signal-regulated Kinase

Abstract: 272, 1395-1401).Here, we examine whether cholesterol-enriched compartments in the plasma membrane are responsible for such differential regulation. Pretreatment of BAEC with a cholesterol-binding antibiotic, filipin, did not inhibit shear-dependent activation of JNK. In contrast, filipin and other membrane-permeable cholesterol-binding agents (digitonin and nystatin), but not the lipid-binding agent xylazine, inhibited shear-dependent activation of ERK. The effect of cholesterol-binding drugs did not appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
159
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(174 citation statements)
references
References 59 publications
14
159
0
1
Order By: Relevance
“…Structure in Plasma Membranes of VSMCs-It has been demonstrated that caveolae-like structures can be disrupted by cholesterol depletion using ␤-cyclodextrin (7,9). To confirm this observation in VSMCs, we examined the effects of ␤-cyclodextrin on cholesterol efflux into the extracellular medium and on cholesterol content of the plasma membrane fraction.…”
Section: Effect Of ␤-Cyclodextrin On Cholesterol Content and Caveolaementioning
confidence: 99%
“…Structure in Plasma Membranes of VSMCs-It has been demonstrated that caveolae-like structures can be disrupted by cholesterol depletion using ␤-cyclodextrin (7,9). To confirm this observation in VSMCs, we examined the effects of ␤-cyclodextrin on cholesterol efflux into the extracellular medium and on cholesterol content of the plasma membrane fraction.…”
Section: Effect Of ␤-Cyclodextrin On Cholesterol Content and Caveolaementioning
confidence: 99%
“…Specifically, the physical association of receptors and signaling molecules with raft domains can be confirmed by using substrates to modulate cholesterol content; for example, studies use ␤-CD to disrupt caveolae-like structures by binding to and sequestering cholesterol from the plasma membrane of intact cells (42,50,51). One previous study (2) has demonstrated an absolute requirement for cholesterol for growth in mouse MM cells, and in this study we similarly characterized the role of cholesterol in human MM cells.…”
Section: Resultsmentioning
confidence: 99%
“…When membrane integrity is breached, for instance by leaching cholesterol (Park et al, 1998) or sequestering membrane cholesterol with filipin (Rizzo et al, 1998), signaling networks are disrupted. A large variety of signaling molecules have been found to be discretely concentrated in detergent-resistant membrane, including GTP-binding proteins, tyrosine kinases, calcium and lipid signaling molecules.…”
Section: Membrane Structurementioning
confidence: 99%
“…Nitric oxide is released shortly after shear stress from osteoblasts and osteocytes (Reich et al, 1990;Smalt et al, 1997b) likely due to activation of endothelial nitric oxide synthase (Klein et al, 2004) similarly to known effects of shear in vascular cells (Boo and Jo, 2003). The rapid activation of nitric oxide in endothelial cells requires, in part, an intact plasma membrane, including lipid rafts (Park et al, 1998) and cyto-skeleton (Knudsen and Frangos, 1997), and this is likely to be true for mechanical release of nitric oxide in bone cells. Endothelial nitric oxide synthase is the predominant nitric oxide synthase isoform in adult bone (Helfrich et al, 1997), and expression of this gene with subsequent increase in nitric oxide production is upregulated by strain in marrow stromal cells (Rubin et al, 2003).…”
Section: Nitric Oxide Signalingmentioning
confidence: 99%